AC electrohydrodynamic propulsion and rotation of active particles of engineered shape and asymmetry. (June 2022) - Diwakar, Nidhi M.; Kunti, Golak; Miloh, Touvia; Yossifon, Gilad; Velev, Orlin D.
Abstract: This review presents the recent progress in the development of active particles driven by alternating-current (AC) electrokinetic effects. These particles propel by asymmetrically dissipating the external energy provided by the fields. An AC field can trigger several electrohydrodynamic mechanisms depending on the field frequency and amplitude, which can also control particle–particle interactions and collective behavior. Recently there has been a strong focus on powering and controlling the motion of self-propelling particles with engineered shape, size, and composition. We introduce a tiered classification of AC field-driven active particles and discuss the fundamental electrohydrodynamic effects acting in individual and multi-particle systems. Finally, we address the limitations and challenges in the current state of AC-field driven engineered particles. Graphical abstract: Image 1